PENGARUH PROFITABILITAS DAN INVESTMENT OPPORTUNITY SET TERHADAP KEBIJAKAN DIVIDEN TUNAI PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BEI PERIODE 2015-2017 - Mujizatul Safinaza; Maslichah Maslichah; Junaidi Junaidi (Universitas Islam Malang, 2019)
ABSTRACT This research was conducted to analyze the effect of profitability and investment opportunity set on cash dividend policy. The sample in this study is a manufacturing company listed on the Indonesia Stock Exchange for the period 2015-2017. Based on the results of testing the hypothesis that has been done, the conclusion is taken as follows. The results of simultaneous testing of profitability and investment opportunity sets influence the cash dividend policy. The test results partially show that profitability variables affect the cash dividend policy. While the investment opportunity set variable partially does not affect the cash dividend policy. R Square test results amounted to 0.694. This means that 44.6% of the cash dividend policy is influenced by profitability and investment opportunity sets while the remaining 55.4% is influenced by other variables such as liquidity, company size and other variables that are not used in this research. For investors, it is wiser to make decisions in consideration that is beneficial for investment. For management, it is wiser to make decisions in determining the amount of dividends.Keywords: Profitability, Investment Opportunity Set and Cash Dividend Policy.